THE THREE LEADERSHIP MODELS: IMPLICATIONS FOR 21ST CENTURY LEADERSHIP (Singaporean Journal of Business Economics and Management, 2013)
This paper is about three leadership models: participative leadership, situational leadership, and charismatic leadership. A review will be conducted on the development of these leadership models and its relative effectiveness on leadership within various organizations. Other leadership models will be mentioned to illustrate their effectiveness on the three selected leadership models. The three leadership models will also be compared and contrasted for their similarities and differences and how they support each other and other leadership models. The need for additional leadership models in the future will also be examined because leadership is an ongoing development as society and technology continue to change. Although there isn't any one leadership trait that will guarantee successful leadership in any given situation; leaders must adapt leadership models within their own leadership styles to become effective leaders within their organization.